Ensino Fundamental de nove anos: articulações necessárias com a Educação Infantil - Lima, Elieuza Aparecida de [UNESP]; Valiengo, Amanda [UNESP] (My University, 2012)
This article leads to reflect on the analysis of contexts of early Childhood Education and Elementary School concerning the space for playtime in the educational routine with groups of children between five and six years old. There was a reflection on official documents about the extension of Elementary School and the presuppositions from the Cultural- -Historical Theory. Actions related to bibliographical research, questionnaire application, photographic and written documentation of playful practices observation, collective meetings with teachers and construction of a toy library have been taken. Specifically on the studied aspect, the make-believe play is the main child activity and may be considered as a mediator from the learning and from the humanization possibilities until about six years old. With this understanding, this issue deserves attention from the government (expressed in public policies), from the teachers and from the school staff in order to offer better conditions of success on the full formation during childhood.

Este artigo leva a refletir sobre as análises de contextos da Educação Infantil e do Ensino Fundamental referentes ao lugar da brincadeira na rotina educacional com turmas de crianças de cinco a seis anos. Refletiu- -se acerca de documentos oficiais sobre a ampliação do Ensino Fundamental e os pressupostos da Teoria Histórico-Cultural. Foram realizadas ações relativas à consulta bibliográfica; aplicação de questionário; ao registro fotográfico e escrito de observações de práticas lúdicas; aos encontros coletivos com professoras e à construção de uma brinquedoteca. Especificamente sobre o aspecto estudado, a brincadeira de faz de conta é a atividade principal da criança e pode ser considerada como mediadora dos aprendizados e possibilidades de humanização até aproximadamente seis anos. Com este entendimento, este assunto merece atenção do governo (expressa nas políticas públicas), dos professores e da equipe escolar, para oferecer melhores condições de êxito para a formação plena na infância.
Nine-year elementary school: needed articulations to early childhood education
Keywords: Brincadeira; educação infantil; ensino fundamental de nove anos; Formação Inicial de Professores; Formação Continuada de Professores